ACTIVITIES OF THE GUARANTEE FUND FOR SERVICING PUBLIC DEBT - Payziyeva Komila (KONFERENSIYALAR, 2025)
This paper explores the role and activities of the Guarantee Fund in servicing public debt, highlighting its importance in ensuring fiscal stability and investor confidence. The Guarantee Fund serves as a financial mechanism that mitigates the risk associated with public debt by providing guarantees for debt repayments. This study examines the structure, functions, and operational procedures of the Guarantee Fund, along with its impact on public debt management. Through an analysis of case studies and empirical data, the paper provides insights into the effectiveness of the Guarantee Fund in maintaining sovereign credit ratings and promoting sustainable economic growth. The findings underscore the significance of the Guarantee Fund in managing financial risks and enhancing the credibility of public debt issuances.